Perbedaan Pengetahuan, Sikap, Motivasiidan Tindakan setelah Diberikan Edukasi Melalui Game (Kotak Pilihan Cerdas) pada Siswa tentang Resiko Gagal Ginjal di SDN 66 Kendari Tahun 2024 - Salfina Salfina; Hartati Bahar; Siti Nurfadilah (Jurnal Medika Nusantara, 2025)
Kidney failure occurs when kidney function suddenly decreases and cannot transport metabolic waste from the body or perform its normal functions. As a result of impaired renal excretion, a substance that is usually excreted from the body accumulates in body fluids. In Indonesia, there is also an increase in cases of kidney failure in children, where according to the Indonesian Pediatrician Association (IDAI) in September 2022 there were 74 cases of Acute Kidney Injury Progressive Atypical that had been reported. The purpose of this study was to determine the differences in knowledge, attitudes, motivations and actions after being given education through the KOPILAS (Smart Choice Box) game to students about the risk of kidney failure at SDN 66 Kendari in 2024. The research method used a quantitative approach, a Pre-Experimental design type using a one group pretest and posttest design. The population of this study was 70 students, while the sample was 56 respondents who were taken using a purposive sampling technique using the Lemeshow formula. The results of the Wilcoxon test showed an increase in knowledge, attitude, motivation, and action after the KOPILAS game was given to students at SDN 66 Kendari in 2025 with each p-value of knowledge (0.000) < alpha (0.05), p-value of attitude (0.000) < alpha (0.05), p-value of motivation (0.000) < alpha (0.05), and p-value of action (0.000) < alpha (0.05). This study was conducted for 21 days.